Reforming the Welfare State: Camden 1965-73 - Mark Swenarton (Footprint)
The housing projects built by the London Borough of Camden in the years 1965-73 belong arguably to the most substantial investigations into the architecture of social housing undertaken in the past half-century. Under borough architect Sydney Cook, Camden aimed to establish a new kind of housing architecture based, not on the Corbusian tabula rasa, but on a radical reinterpretation of traditional English urbanism.